Peranan Kepala Sekolah dalam Meningkatkan Kualitas Pendidikan di SMAN 2 Muaro Jambi - Anggraini, Liza; Muspawi, Mohammad; Rahman, K. A. (Jurnal Ilmiah Dikdaya, 2024)
: Quality education is education that can produce graduates with competencies and abilities in both vocational and academic fields, based on social, personal competencies and good behavioral values. The principal is the main driver for the development and progress of the school and is responsible for increasing the success of students and their programs. The aim of this research is to determine the role of school coconuts in improving the quality of education at Senior High School 2 Muaro Jambi. The subjects of this research are school principals and teachers. Data collection techniques include; observation, interviews and documentation. The data analysis technique used is descriptive analysis technique, namely analysis that explains the facts of the data as they are, excluding subjective points of view. This method is used to analyze qualitative data.